Peningkatan Kinerja Panel Surya 10 Wp Menggunakan Solar Tracker Berbasis ESP32 - Nugraha, Noviyanti; Hartawan, Liman; Marsono, Marsono; Mochamad Rachman, Randi; Adi, Seril (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2026)
Solar panels convert solar radiation into electrical energy. However, solar panels installed statically at a fixed angle have limitations in optimally capturing sunlight intensity due to the sun’s changing position throughout the day. The objective of this study is to develop a design and prototype for a solar power generation system. The PV modules used, both for solar tracking and non-tracking systems, each have a capacity of 10 Wp. The solar tracking system design is based on an ESP32 microcontroller, which uses a light-dependent resistor (LDR) sensor to detect sunlight intensity from different directions. Test data readings via IoT can be viewed on a smartphone or PC using the Blynk app. The solar power plant with a tracking system has been successfully designed, built, and tested to compare its power output with that of the non-tracking system. The average power generated by the tracking system was 6.1 watts, while the maximum power generated by the non-tracking system was 5.7 watts. The percentage difference in power between the tracking and non-tracking systems was approximately 5.7%.